Is Raman Optical Activity Spectroscopy Sensitive to β‐Turns in Proteins? Secondary Structure and Side‐Chain Dependence. Issue 22 (9th October 2018) - Mensch, Carl; Johannessen, Christian
Abstract: β‐turns are essential for the structure and function of proteins. The spectroscopic technique Raman optical activity (ROA) has been suggested to be sensitive to such structural elements of proteins in solution. Three spectral features have been reported to mark β‐turns in protein ROA spectra: being a negative band at 1220 cm −1, positive intensity around 1290 cm −1 and negative intensity around 1340–1380 cm −1 . In this work, density functional theory calculations demonstrated that these assignments are inaccurate as these spectral regions are not robust and sense the exact secondary structure surrounding the β‐turn as well. Furthermore, it was demonstrated that the amino acid side‐chains affect the exact ROA patterns which can direct future research to perform a systematic analysis of the contributions of the side‐chains. Abstract : Raman optical activity senses β‐turns but does not display marker bands.